Geomorphic evolution and neotectonics of the Qianhe River Basin on the southwest margin of the Ordos Block, North China. (1st June 2019) - Zhang, Tianyu; Fan, Shuanghu; Chen, Shue; Li, Sanping; Lu, Yudong
Graphical abstract: Highlights: Geomorphic evolution was studied based on geomorphic indices and field surveys. Geomorphic parameters reveal obvious relationships with tectonic activity. Geomorphic evolution is controlled by northeastward extrusion of the Qinghai-Tibetan Plateau. The southwestern Ordos Block undergoes strong northwestward tectonic tilting. Abstract: The Qianhe River Basin is located at the convergence zone of the northeastern margin of the Tibetan Plateau (NETP), the Ordos Block and the Qinling Mountains. A tectonic geomorphology study of the Qianhe River is significant for providing a deeper understanding of the tectonic transition between the NETP and the Ordos Block and the dynamic relationship of these three tectonic units. Based on Advanced Spaceborne Thermal Emission and Reflection global digital elevation model (ASTER-GDEM) data and geographic information system (GIS) techniques, four tectonic geomorphic indices, the hypsometric integral (HI), stream length-gradient (SL), drainage basin asymmetry (AF), and drainage basin shape (BS), were calculated and analyzed. Geologic evidence from field surveys, deformation measurements, and fault slip rate estimates was also obtained to further discuss the tectonic activity and tectonic geomorphic evolution model. Through analytical comparisons, we proposed that the variations in the applied geomorphic index values were not significantly affected by climate and lithology but indicated variations in related tectonic activity. The geomorphic index value analysis suggested relatively strong tectonic activity in Liupanshan Mountain and Longshan Mountain and northwestward tectonic tilting of the southwest margin of the Ordos Block. The actual mechanisms responsible for the observed variations in the Qianhe River Basin are the rapid uplift and northeastward extrusion of the Qinghai-Tibetan Plateau and the local tilting uplift of the southwestern Ordos Block.